A comparative study on whipping as punishment for muslim women offenders - Othman, Yuhanza; Erlen Joni, Ekmil Krisnawati; Mahat, Ida Rahayu (2011)
The provisions for the sentence of whipping exist in both Syariah and civil law. The Criminal Procedure Code 1999 contains clear provisions pertaining to whipping on male offenders only because Section 289 of this Code expressly states that female offenders are exempted from it. The Syariah law, however, does not distinguish between male and female offenders in imposing this sentence as all offenders shall suffer the same modes of sentencing when they have committed any crime. Nevertheless, Syariah Court judges in Malaysia have been reluctant to impose whipping sentence on women offenders until recently. In 2009, the Malaysian public was shocked when the Syariah Court handed the whipping sentence to Kartika Seri Dewi Sukarno and Noorazah Baharuddin for consuming intoxicating beer and three other female offenders for sexual intercourse out of wedlock. The Syariah law in Malaysia provides for the punishment of whipping in several offences such as drinking, intoxication, incest and adultery. However, the procedure on whipping female Muslim offenders is ambiguous. Thus, this research shall study and analyse the procedural guidelines on the punishment of whipping for female Muslim offenders by analysing the existing law in Malaysia and comparing the local law of whipping with the law in other countries. It is hoped that this research would provide a clear description, explanation and recommendation in improving the enforcement and practical application of Syariah law in Malaysia on whipping in rehabilitating the convict and deterring the general public from committing similar offences in the future.